Development of oats flour and bitter gourd fortified cookies: Effects on physicochemical, antioxidant, antimicrobial, and sensory attributes. - Rehenuma Tarannum; Asraful Alam; Md Sakib Hasan; Golam Rabby; Ananya Raiyan; Rashida Parvin; Mahfujul Alam; Md Ashrafuzzaman Zahid (PLoS ONE)
The objective of this study was the develop of fortified cookies enriched with oats flour and bitter gourd powder and monitoring the effects of these enrichments on the physicochemical, antioxidant, antimicrobial, and sensory attributes. This study was subjected to four treatments: control (0% oats flour and bitter gourd powder), T1 (10% oats flour), T2 (3% bitter gourd powder), and T3 (7% oats flour and 3% bitter gourd powder). Various physical properties of the cookies, including weight, thickness, diameter, spread ratio, baking loss, pH, and color values (L*, a*, and b*), were measured. Proximate analysis revealed moisture (4.23-4.70%), ash (1.17-1.67%), fat (13.62-15.09%), crude protein (7.02-7.36%), carbohydrate (71.78-72.97%), energy (442.62-452.40 kcal), and crude fiber (8.02-3.33%). Mineral contents included Na (787-754 mg/100g), Ca (873-435 mg/100g), and Zn (66.7-58.8 mg/100g). Additionally, DPPH free radical scavenging activity ranged from 13.14 to 75.51%, while TBARS activity varied from 0.78 to 1.33 mg MDA/kg. T2 cookies exhibited the highest antimicrobial activity, with control cookies showing the lowest. The 5-point hedonic scale indicated that T2 cookies had lower overall acceptability, while T3 cookies were better received. In conclusion, the study suggests that fortified cookies have a more significant impact than regular or control cookies.